2009
DOI: 10.1186/1758-2555-1-28
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic fracture-dislocation of the hip following rugby tackle: a case report

Abstract: Posterior fracture-dislocation of hip is uncommonly encountered in rugby injuries. We report such a case in an adult while playing rugby. The treating orthopaedician can be caught unaware and injuries in such sports can be potentially misdiagnosed as hip sprains. Immediate reduction of the dislocation was performed in theatres. The fracture was fixed with two lag screws and a neutralization plate. This led to early rehabilitation and speedy recovery with return to sporting activities by 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Several contour lines seen at standard anteroposterior (AP) pelvic radiography aid in systematic interpretation (Fig 3) (18). Both the iliopectineal line (comprising the anterior column of the acetabulum) and the ilioischial line (comprising the posterior column) should be continuous and Hip dislocations in sporting activities are rare, representing only 2%-5% of hip dislocations, but may occur in high-velocity sports such as football and rugby (19)(20)(21). The position of the leg at the time of the trauma determines if the hip dislocates with or without fracture of the acetabulum or femoral head.…”
Section: Radiographic Anatomy Of the Hipmentioning
confidence: 99%
“…Several contour lines seen at standard anteroposterior (AP) pelvic radiography aid in systematic interpretation (Fig 3) (18). Both the iliopectineal line (comprising the anterior column of the acetabulum) and the ilioischial line (comprising the posterior column) should be continuous and Hip dislocations in sporting activities are rare, representing only 2%-5% of hip dislocations, but may occur in high-velocity sports such as football and rugby (19)(20)(21). The position of the leg at the time of the trauma determines if the hip dislocates with or without fracture of the acetabulum or femoral head.…”
Section: Radiographic Anatomy Of the Hipmentioning
confidence: 99%
“…Letournel and Judet [13] showed that the posterior rim of the acetabulum bears the impact from the femoral head in this leg position. Acetabular fractures from sports are a rare occurrence and cases have often involved the same mechanism of injury as in our case [14,15]. Joint reactive force (JRF) is involved in hip joint biomechanics and represents the sum of the mechanical forces acting across the hip joint.…”
Section: Discussionmentioning
confidence: 97%
“…But to our knowledge, there is no case reported that have a pure hip dislocation when playing non-contact sport like tennis. In English literature there are 21 traumatic hip dislocations with and without fracture in sports activity [2][3][4][5][6][7][8]. Among all these -6 rugby, 5 soccer, 2 futsal and one each water skiing, equestrian, gymnastic, jogging, skiing, biking, sledge, basketball player had traumatic hip dislocation-only five of them were pure dislocations.…”
Section: Discussionmentioning
confidence: 99%